A comparative study of organic and conventional farming system in relation to environmental and financial sustainability - Obra, Ella Loraine D.; Rimando, Charmagne Anne M. (2013)
Agricultural practices bear an impact on the environmental sustainability in the Philippines. Most agricultural actors aim to have higher yields and earn higher levels of production income. Raw materials for food production are basically come from the agricultural sector. Increasing population entails a greater demand for food. To gain higher profits and meet the increasing food demands, agriculture towards modernization. Modern practices entail a high dependence on demands in the short-run. However, it will not ensure the long-run sustainability of the farming environment. This study compares the environmental and financial sustainability of organic and conventional farming systems. It assesses which farming system is more financially and environmentally sustainable. The researchers have chosen barangay Balili, La Trinidad, Benguet as the area of study. Quota sampling has been applied to determine the number of organic and conventional farm producers participating in the study. Agricultural offices and markets such as the Municipal Agriculturist Office and Benguet State University Market Cooperative have been very important sources of information in this study. The primary data used in this study includes perceptions, income and cost of production, suggestions and practices employed by the farmers. On the other hand, the secondary data used is the Vegetable consumption and production in the Philippines (1990-2005) presented by S. Conception. The result shows that organic farming employ practices that are more environmentally sustainable than conventional farming. In terms of financial sustainability the difference between the gross and net annual income of these two farming systems is not statistically significant. Farmers suggest that a greater subsidy from the government will encourage them to shift to more sustainable farming practices -- Author's abstract.
Thesis (Bachelor of Arts in Social Sciences)--University of the Philippines Baguio, 2013.
Includes bibliographical references (leaves 89-93)
Keywords: Sustainable agriculture -- Philippines; Organic farming -- Philippines